Soil and Water Loss (Run-Off) Studies Under Different Vegetative Covers on 0.5 and 1.0% Slope at Kota - singh, Gurmel; Dayal, Rajbans; Bhola, S.N. (Journal of Soil and Water Conservation, 2022)
The soils of Kota region are having flat to undulating topography. The slope percentage is generally upto 1.0%. Soils are heavy in texture, having low infiltration rate and slow permeability and thus a greater part of the rainfall received during the year is lost as run-off. This water running down the slopes constitutes a destructive force and leads to the formation of gullies and ravines. There is a great need for controlling the run-off and to adopt various measures which will help in reduc’ng the soil and water loss/ Soil and water loss is mainly influenced by rainfall, its intensity and duration (ii) soil (iii) percen-tage of slope and (iv) vegetation. Vegetation is the only factor which can be controlled. It protects the soil from the destructive effects of rain water and conserved water promotes the growth of vegetation. The effectiveness of the various vegetative covers can be evaluated by measuring the soil and water loss which can serve as a guide in planning soil and water conservation measures. With this object in view, a study to measure soil and water loss was carried out at 0.5 and 1.0% slope under vegetative crops covers.